2019
DOI: 10.1128/mbio.02327-18
|View full text |Cite
|
Sign up to set email alerts
|

Glycyl Radical Enzyme-Associated Microcompartments: Redox-Replete Bacterial Organelles

Abstract: An increasing number of microbes are being identified that organize catabolic pathways within self-assembling proteinaceous structures known as bacterial microcompartments (BMCs). Most BMCs are characterized by their singular substrate specificity and commonly employ B12-dependent radical mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 76 publications
(157 reference statements)
1
40
0
Order By: Relevance
“…In addition to the widespread HGT of loci evident from their distribution across phyla (Figure 4), individual shell proteins provide links, such as the BMC‐T dp of EUT3 and SPU6. Likewise, with our observations we can propose steps in the evolution of the encapsulated catalysis; in the canonical PDU1AB and the recently described GRM4 [36, 42], the colors of all shell the same in both loci (Supplementary Data: Locus diagrams). Comparison of the locus diagrams reveals the same gene order, with the PDU signature enzymes interchanged with the GRM4 signature enzyme.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the widespread HGT of loci evident from their distribution across phyla (Figure 4), individual shell proteins provide links, such as the BMC‐T dp of EUT3 and SPU6. Likewise, with our observations we can propose steps in the evolution of the encapsulated catalysis; in the canonical PDU1AB and the recently described GRM4 [36, 42], the colors of all shell the same in both loci (Supplementary Data: Locus diagrams). Comparison of the locus diagrams reveals the same gene order, with the PDU signature enzymes interchanged with the GRM4 signature enzyme.…”
Section: Discussionsupporting
confidence: 80%
“…Encasing the pathway inside BMCs is essential, since this prevents the toxic acetaldehyde intermediate to damage proteins and RNA/DNA in the cytoplasm [17,37]. The generated reductants are oxidized inside the BMC, while it has been hypothesized that electrons may also be shuttled to the cytosol via specific shell proteins acting as redox carriers [8,17,18,36]. Our metabolite analysis showed enhanced flux via the ATP generating acetate branch in L. monocytogenes, and a reduced flux via the NAD+ regenerating ethanol branch in a 2:1 molar ratio resulting in surplus NADH.…”
Section: Discussionmentioning
confidence: 99%
“…The observed unbalanced production of acetate and ethanol in a 2:1 molar ratio suggests a surplus of NADH, and this requires additional NAD+ regeneration reactions to restore the redox balance. As discussed in previous studies, BMC is a redox-replete compartment which can generate reductants internally or facilitate the transfer of electrons from the cytosol across the shell [8,36]. Recently it has been shown that L. monocytogenes uses a distinctive anaerobic flavin-based EET mechanism to deliver electrons to iron (Fe 3+ ) or to fumarate via membrane-bound fumarate reductase [2].…”
Section: Flavin-based Eet Linked With Bmcs Maintains Redox Balance Ofmentioning
confidence: 99%
“…Alternatively, their use may suggest O 2 limitation, possibly due to increased heterotrophic biological O 2 demand; pyruvate formate-lyase employs a radical mechanism that generates toxic reactive oxygen species in the presence of oxygen (21). This result was paradoxical, as the biofilm was maintained under light (and, therefore, presumably O 2 ) during the labeling period, but it may reflect either local conditions where rapid heterotroph respiration of organic C fluxes from the cyanobacteria resulted in pockets of hypoxia or internal microcompartments to protect these enzymes from oxygen (22).…”
Section: Nomentioning
confidence: 99%